Clinical Profile of Pelvic Inflammatory Disease (PID). (Faridpur Medical College Journal, 2017)
Pelvic inflammatory disease is an important and major health problem in Bangladesh. This study was undertaken to find out the common clinical presentation of pelvic inflammatory disease in relation to reproductive health of women in our country. This study has been carried out at the outpatient department of Obstetrics and Gynaecology, Sher- EBangla Medical College Hospital, Barisal, during period from January 2010 to December 2010. In this descriptive type of cross sectional study, total number of 150 patients suffering from PID were selected. Details history and thorough clinical examination was performed with the aim of find out clinical presentation of PID. Related investigations were done. This study shows that 54% belongs to age group 26-35 years, 90% patients were married and 4% were separated, 90% were house wifes, 60% patients were from lower socio-economic status. All patients complained lower abdominal pain, 60% had vaginal discharge, 80% patients delivered solely at home and 73.33% were delivered by untrained birth attendants at home. Pelvic inflammatory disease is detrimental to reproductive health and makes the women cripple physically, mentally and socially. So appropriate measures e.g. better obstetric and delivery care, family planning care, safe way of pregnancy termination; health education etc. should be made for our women.Faridpur Med. Coll. J. Jan 2017;12(1): 25-30